Care4HIP: An Embedded System Design for Discerning Hear-Impaired People in Traffic - Akyol, Kemal; Karacı, Abdulkadir; Tiftikçi, Muhammed (Politeknik Dergisi, 2022)
Embedded systems are designed for many different applications including navigation, thief warning, smart home, tracking. We designed an embedded system, Care4HIP, Care for Hearing Impaired People, which presents a solution for discerning the hear-impaired people in traffic. Our solution aims that drivers will be able to notice the hear-impaired people. Care4HIP calculates the locational information of these people which close to the vehicle and determines the direction of these people with respect to the vehicle. Location information refers to the latitude and longitude data of each person's location. The proposed system involves server, mobile and embedded system based applications. We think that Care4HIP offers an original and practical solution with minimal overhead for hear-impaired people.
Keywords: Engineering; Hearing-impaired people; traffic; embedded system; Raspberry Pi 3+.; Mühendislik